أهمية النسب المالية في التحليل المالي للقوائم المالية بالمؤسسة الإقتصادية-دراسة حالة بمؤسسة توزيع الكهرباء والغاز بولاية الأغواط - مولاي هناء; قفاف إحسان; حساب محمد لمين (جامعة عمار ثليجي الاغواط, 2022)
This study, entitled "The role of financial analysis in the diagnosis of the financial position of the economic institution", aimed to highlight the importance of financial analysis and address the analysis of the financial position of the Electricity and Gas Distribution Corporation in Laghouat , for the period (2019 to 2020), by applying financial diagnostic tools and methods to financial statements using financial balance indicators and some financial ratios based on the budget and the calculation of results, this study has reached several conclusions, the most important of which has been: That the institution is in a bad position and this through the various ratios that we calculated and then analyzed to know the real financial position of the institution and make the appropriate decisions for it as the institution achieved negative numbers related to the net result and this indicates that the institution achieved losses during the years of study.